2013
DOI: 10.1007/s00403-013-1429-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Foxp3 and interleukin-17 in lichen planus lesions with emphasis on difference in oral and cutaneous variants

Abstract: Foxp3 is a specific marker for regulatory T cells (Tregs), and interleukin (IL)-17 is the signature cytokine of T-helper (Th) 17 cells. Recent studies suggested that Foxp3+ Tregs and IL-17+ Th17 cells may be involved in pathogenesis of lichen planus (LP). The objectives of this study were to examine the immunoexpression of Foxp3 and IL-17 in archival paraffin-embedded biopsy specimens from 80 cases of LP (oral LP, n = 42; cutaneous LP, n = 38) and compare against normal control tissues (oral mucosa, n = 10; sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 26 publications
4
40
1
4
Order By: Relevance
“…cells in OLP than in the NSI group and that they were situated in the superficial connective tissue, subjacent the epithelium corroborating the results of others [16,18,20]. Double IF demonstrated that the FoxP3 ?…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…cells in OLP than in the NSI group and that they were situated in the superficial connective tissue, subjacent the epithelium corroborating the results of others [16,18,20]. Double IF demonstrated that the FoxP3 ?…”
Section: Discussionsupporting
confidence: 91%
“…cells were infrequent overall, but were more common in the NSI tissues than the OLP tissues, and were found deeper in the connective tissue. These findings contrast with the reports from others [13,18], who described more sub-epithelial IL17 ? cells in OLP in comparison with normal mucosal controls.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…15 CD4þCD25þ Foxp3þ regulatory T cells have been shown to be associated with OLP, 30,44,51 as has dysregulation of Th17 cells 45,51 and the presence of CD3-IL-17þ cells. 15 Furthermore, the disturbed balance between Foxp3þ cells and IL-17 cells in OLP suggests altered local immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Shen et al . demonstrated the increased expression of Foxp3 and IL‐17 in LP lesions including oral and cutaneous variants.…”
Section: Pathogenesismentioning
confidence: 99%